Formation mechanism of the metallic nanostructures using pulsed axial electrothermal plasma accelerator - Kolyada, Yu.E.; Fedun, V.I.; Tyutyunnikov, V.I.; Savinkov, N.A.; Kapustin, A.E. (Вопросы атомной науки и техники, 2013)
Paper is devoted of the formation mechanism of metal the nanoparticles in the development of high-current pulsed electric discharge in a limited volume at atmospheric pressure. The original design of the axial electrothermal plasma accelerator was used to create the discharge operating in the gas-dynamic mode. The analysis of chemical composition and dimensions of the formed particles was carried out. It is established that formation of nanoparticles caused solely through the mechanism of nonequilibrium condensation of supersaturated vapor. Досліджується механізм формування металевих наночастинок при розвитку потужнострумового імпульсного електричного розряду в обмеженому обсязі при атмосферному тиску. Для створення розряду використовувалася оригінальна конструкція електротермічного плазмового аксіального прискорювача, працюючого у газодинамічному режимі. Проведено аналіз хімічного складу і розмірів синтезованих частинок. Встановлено, що формування наночастинок обумовлено виключно за рахунок механізму нерівноважної конденсації пересиченого пару. Исследуется механизм формирования металлических наночастиц при развитии сильноточного импульсного электрического разряда в ограниченном объёме при атмосферном давлении. Для создания разряда использовалась оригинальная конструкция электротермического плазменного аксиального ускорителя, работающего в газодинамическом режиме. Проведён анализ химического состава и размеров синтезированных частиц. Установлено, что формирование наночастиц обусловлено исключительно за счёт механизма неравновесной конденсации пересыщенного пара.